Business Models and Innovation Obstacles in Iran: A New Framework - Salamzadeh, Yashar; Rezai, Maryam (Journal of Entrepreneurship, Business and Economics; Vol 5 No 1 (2017), 2016)
Employing appropriate and up to date Business models in Organizations is so important due to the fact that it is the strategy which shows the main logic of a corporation in creating values in organiza-tions. It is important to the extent that not employing an appropriate and up to date business model will prevent the organizations fulfilling their aims, even if they employ high technology or diverse resources. In fact, economical value of a technology is unknown until corporations employ an appro-priate form of business model. It can be said that, those corporations employing more appropriate business models for a technology achieve more value than the corporations discovering that technolo-gy. A good business model is the basis of each successful organization, no difference the investment is new or it's an already established one. Due to the importance of this issue, in this study, we try to identify the main reasons for not being up to date or not developing business models in organizations. We do this by reflecting upon the results of credible and up to date researches in the area of different business models and obstacles or challenges facing different organizations. In line with what was said above, we employed library research, extracting updating obstacles in business models, ques-tionnaire and field research for data collection process. Determining reliability and validity of the questionnaire, we distributed it among 198 corporations of management counseling in Tehran prov-ince. This research follows positivism paradigm and is practical, quantitative, and inductive. The results lead to the discovery of 35 cases of the main reasons of not being up to date and developed in using business models. As there was no basis for categorizing variables and formerly defined catego-ries, in order to maximize the correlation between variables and factors, calculating the factorial ratio and determining the intended factors, we employed factorial design. Using this statistical technique, the variables were categorized in 4 kinds of obstacles: strategic, information, management, and sys-tem. At the end these are ranked using fuzzy Topsis technique. The results of ranking show the im-portance order of obstacles as follows: Informational factors, Systematic factors, managerial factors & strategic factors. Research paper Reference to this paper should be made as follows: Salamzadeh, Y. Rezai, M. (2017). “Business Models and Innovation Obstacles in Iran: A New Framework”, Journal of Entrepreneurship, Business and Economics, Vol. 5, No. 1, pp. 108–139.